Influence of lymphovascular invasion on outcome of colon cancer - Shakir Motib, Mohammed; Hasan Mustaf, Alaa Hasan Mustaf; Faraj Ali Alrubaye, Mohammed; Ali Jasim Al-Hamami, Hayder (Diyala Journal of Medicine, 2024)
Background: Colon cancer is the third most common type of cancer. High lymphovascular levels are linked to a number of cancers, including colon cancer, while lymph vascular invasion levels as a predictor of outcome are not well understood. Objective: Determine the influence of lymphovascular invasion on the recurrence of colon cancer. Patients and Methods: it was collected 126 colon cancer patients who had surgery and additional chemotherapy. The patients attended in the Baquba teaching hospital oncology centre and the Al Jawad oncology centre of Alkadhemiya hospital. Results: it was shown in this study that the high percentage ages of colon cancer patients was between 55-60 years, and there were more in women (57 %) than in men (43 %). The most common stage of the tumours was stage 3 (42.9 %), and in grade 2 (76.2 %). In terms of return, in this study, 71.4 % of people who had lymphovascular invasion positive and had a return of cancer in a percentage 73.3% of colon cancer patients. Conclusion: LVI plays an essential role for increasing recurrence of colon cancer, and there were a strong link between them.